2021
DOI: 10.1152/ajpendo.00203.2020
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity blunts the insulin- and amino acid-induced stimulation of translation initiation and protein synthesis in skeletal muscle of neonatal pigs

Abstract: Extrauterine growth restriction in premature infants is largely attributed to reduced lean mass accretion and is associated with long-term morbidities. Previously, we demonstrated that prematurity blunts the feeding-induced stimulation of translation initiation signaling and protein synthesis in skeletal muscle of neonatal pigs. The objective of the current study was to determine whether the blunted feeding response is mediated by reduced responsiveness to insulin, amino acids, or both. Pigs delivered by Cesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 66 publications
5
23
0
Order By: Relevance
“…Insulin-stimulated glucose uptake is crucial for muscle contraction. Insulin is a powerful synthetic signal that significantly stimulates muscle protein synthesis ( 39 ). Classical insulin signaling pathways and anabolic stimuli, including PI3K, 3-phosphoinositide-dependent kinase 1 (PDK1), AKT, mTOR, and p70S6K, activate protein synthesis and thereby promote muscle growth ( 40 , 41 ).…”
Section: Molecular Mechanism Of Diabetic Muscular Atrophymentioning
confidence: 99%
“…Insulin-stimulated glucose uptake is crucial for muscle contraction. Insulin is a powerful synthetic signal that significantly stimulates muscle protein synthesis ( 39 ). Classical insulin signaling pathways and anabolic stimuli, including PI3K, 3-phosphoinositide-dependent kinase 1 (PDK1), AKT, mTOR, and p70S6K, activate protein synthesis and thereby promote muscle growth ( 40 , 41 ).…”
Section: Molecular Mechanism Of Diabetic Muscular Atrophymentioning
confidence: 99%
“…In this study, we investigated how intermittent bolus and continuous feeding modalities impact muscle anabolic signaling and protein synthesis, SC abundance, myonuclear accretion, and body composition in a preterm neonatal pig model of the premature infant ( 27 ). A key motivation for this study was the observation that, although feeding, insulin, and amino acids all promote anabolic signaling and protein synthesis in skeletal muscle in pigs born preterm and at term, the magnitude of the response is blunted in preterm compared with term pigs ( 25 , 26 ); if persistent, this could mitigate any advantage of intermittent feeding following premature birth.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with full-term pigs, prematurity produced a marked reduction in LD muscle insulin and amino acid signaling to mTORC1 after feeding. More recently, we showed that mTORC1 signaling and protein synthesis in skeletal muscle are blunted in response to equivalent and sustained increases in both insulin and amino acids in preterm compared with term pigs during hyperinsulinemic and hyperaminoacidemic clamps ( 26 ). This blunted insulin- and amino acid-induced mTORC1 activation was associated with reduced Akt phosphorylation and mTOR·Rag association, respectively, in muscle of preterm compared with term pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucine elicited an even greater growth response to the lower protein milk replacer but did not increase growth when added to the high protein formula that provided 12 g protein per kg-day. Protein synthesis of preterm pigs provided 16 g per kg-d of amino acids is lower compared with term pigs (22). Similar to human infants, fetal and postnatal growth rates are related for pigs (23) and small term pigs grow slower than normal birth weight littermates (24).…”
Section: Introductionmentioning
confidence: 92%